Manual of Mutrition - Great Britain. Ministry of Agriculture, Fisheries and Food. (London : HMSO, 1995)
From proteins to processing, digestion to diet, this manual takes a detailed look at the broad science of nutrition. The roles of nutrients in the body, the foods that provide them and effects of cooking and processing are described. Guidance is also given on meal and diet planning.
Keywords: Food; Human physiology; Education